PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING MENGGUNAKAN APLIKASI EDMODO TERHADAP MINAT DAN HASIL BELAJAR SISWA KELAS XI SMA NEGERI 1 DOLOK PANRIBUAN TAHUN AJARAN 2021/ 2022 - DELANTRI AGUSTINA GULTOM; MASNI VERONIKA SITUMORANG; GUNARIA SIAGIAN (JURNAL ILMIAH KOHESI, 2022)
The purpose of this study is to illustrate what the results of the influence of the PBL model assisted by edmodo media on class XI students of SMA Negeri 1 Dolok Panribuan look like. In addition, italso wants to prove whether students' interests and learning outcomes have significant differences before and after treatment. Analysis of this data uses the SPSS program from validityto hypothesis. From the results of the study, the average value of experimental class 2 was obtained using an edmodo-assisted PBL model with a standard deviation of 92. 17 average values of experimental class 1 using a PBL model of 70.81 with a standard deviation of 9.495, and a control mean value of 57.79 with a standard deviation of 10.531 . As for the comparison of learning outcomes in the N-Gain test, it was obtained: The N-gain of experimental class 2 using the edmodo-assisted PBL model is g = 0.7 is the tingi category, while the N-gain of experimental class 1 using the PBL model is g = 0.402 is a medium category, N-gain class control is g = 0.27 is a low category. Therefore, the improvement in experimental class learning outcomes is higher than the increase in control class learning outcomes. This corresponds to the value of sig.( 2- tailed) = 0.000 on ANOVA Sig.(2 - tailed) test = 0.00,< 0.05, then Ho was rejected. So it can be concluded that there are significant differences in "The Effect of Edmodo-Assisted Problem Based Learning Learning Model on Student Interest and Learning Outcomes on Immunity System Material class XI SMA Negeri 1 Dolok Panribuan T.A. 2021 / 2022."